Occupational Stress and the Quality of Life of Nurses in Infectious Disease Departments in China: The Mediating Role of Psychological Resilience - Yan, Jiaran; Wu, Chao; Du, Yanling; He, Shizhe; Shang, Lei; Lang, Hongjuan (Frontiers in Psychology, 2022)
Aim: We aim to explore the impact of occupational stress on the quality of life of nurses in infectious disease departments and to explore the mediating role of psychological resilience on this impact. Background: Sudden public health events and the prevalence of infectious diseases give nurses in infectious disease departments a heavy task load and high occupational stress, which can affect their quality of life, which is closely related to the quality of clinical care they provide. There are few studies on occupational stress, psychological resilience, and quality of life of nurses in infectious disease departments. Methods: We collected data from infectious-disease-specialized hospitals or infectious disease departments of general hospitals in China. In total 1,536 nurses completed questionnaires: the Effort-reward Imbalance Questionnaire, the Connor-Davidson Resilience Scale, and the World Health Organization Quality of Life Brief Scale. We use a structural equation model to test our hypothesis. Results: Occupational stress detection rates of nurses in infectious disease departments were high, and were significantly negatively correlated with their quality of life. We find that psychological resilience partly mediates the link between occupational stress and quality of life. Conclusion: Occupational stress of nurses in infectious disease departments has an important impact on their quality of life, and psychological resilience plays a partial mediating role on this impact. Implications for Nursing Management: Hospital managers can benefit from paying attention to the occupational stress of nurses and helping to improve the quality of life of nurses by alleviating this occupational stress and improving psychological resilience.